Re–examining Bhagwati hypothesis: the case of some selected countries in Sub-Saharan Africa - Ibrahim, Muazu; Koomson, Isaac; Aluko, Olufemi Adewale; Opoku, Eric Evans Osei (Routledge, 2021)
Bhagwati hypothesis opines that the overall impact of foreign direct investment (FDI) on economic growth is conditioned on countries’ level of integration with the international market. We test this hypothesis for some selected countries in sub-Saharan Africa (SSA). Does this hypothesis hold given our sample evidence? Yes! No! Maybe! We explain why. By invoking the sample splitting and threshold estimation technique, we find that the two measures of openness (trade openness and exports) mediate the FDI-economic growth relationship in three countries and this is an indication of complete Bhagwati hypothesis in these countries. Also, we find that, given the measure of openness, four countries exhibit incomplete Bhagwati hypothesis. Finally, we find no support for the Bhagwati hypothesis for most countries. Based on these findings, we argue that the validity of the Bhagwati hypothesis may be contingent on both country characteristics and the indicator of openness.